2018
DOI: 10.1128/jvi.00773-18
|View full text |Cite
|
Sign up to set email alerts
|

The Major Tegument Protein of Bovine Herpesvirus 1, VP8, Interacts with DNA Damage Response Proteins and Induces Apoptosis

Abstract: VP8, the gene product in bovine herpesvirus-1 (BoHV-1), is a major tegument protein that is essential for virus replication The major DNA damage response protein, ataxia telangiectasia mutated (ATM), phosphorylates Nijmegen breakage syndrome (NBS1) and structural maintenance of chromosome-1 (SMC1) proteins during the DNA damage response. VP8 was found to interact with ATM and NBS1 during transfection and BoHV-1 infection. However, VP8 did not interfere with phosphorylation of ATM in transfected or BoHV-1-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In this study, for the first time, we revealed that BoHV-1 infection of bovine kidney cells induced DNA damage ( Figure 1 ), and that the inhibition of ROS production by either NAC or DPI could rescue the virus infection-induced DNA damage and cell death ( Figure 2 ). Importantly, during our preparation of this manuscript, a paper has been published revealing that BoHV-1 tegument protein VP8 induces cell apoptosis through blocking the DDR proteins including ataxia telangiectasia mutated (ATM), phosphorylates Nijmegen breakage syndrome (NBS1) and structural maintenance of chromosome-1 (SMC1), which may consequently lead to the inhibition of DNA repair [ 45 ]. Thus, it is reasonable to speculate that the induction of DNA damage correlates with BoHV-1-caused cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for the first time, we revealed that BoHV-1 infection of bovine kidney cells induced DNA damage ( Figure 1 ), and that the inhibition of ROS production by either NAC or DPI could rescue the virus infection-induced DNA damage and cell death ( Figure 2 ). Importantly, during our preparation of this manuscript, a paper has been published revealing that BoHV-1 tegument protein VP8 induces cell apoptosis through blocking the DDR proteins including ataxia telangiectasia mutated (ATM), phosphorylates Nijmegen breakage syndrome (NBS1) and structural maintenance of chromosome-1 (SMC1), which may consequently lead to the inhibition of DNA repair [ 45 ]. Thus, it is reasonable to speculate that the induction of DNA damage correlates with BoHV-1-caused cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…By this simple yet elegant mechanism, viruses exploit the cell intrinsic ubiquitin-proteasome system to defeat antiviral immunity. Well-known examples of viral exploitation of DDB1 and/or CRLs include the hepatitis B virus (HBV) protein HBx [84,89,90,91,92], the HIV-1- and HIV-2-encoded protein Vpr [93,94,95,96,97,98,99,100,101,102], HIV-2 Vpx [103,104,105,106,107,108,109], parainfluenza virus (PIV) V proteins [78,110,111,112], bovine herpesvirus 1 (BoHV-1) VP8 [113,114], murine gamma herpesvirus (MHV68) M2 [115], as well as the cytomegalovirus proteins pM27 [116,117,118], pUL35 [119], and pUL145 [120].…”
Section: Exploitation Of Ddb1 and Crls By Virusesmentioning
confidence: 99%
“…VP8, the major tegument protein of BoHV-1, is a product of the U L 47 gene [ 14 ], and plays a versatile role in viral replication [ 4 ], induction of humoral and cell-mediated immunity [ 15 ], alteration of host defense mechanisms [ 16 ], and cell death or apoptosis [ 17 ]. It is a late protein, and is conserved throughout the alphaherpesvirus family [ 14 ].…”
Section: Introductionmentioning
confidence: 99%